The full‐length Auxin Response Factor 8 isoform ARF8.1 controls pollen cell wall formation and directly regulates TDF1, AMS and MS188 expression. (19th January 2023) - Ghelli, Roberta; Brunetti, Patrizia; Marzi, Davide; Cecchetti, Valentina; Costantini, Marco; Lanzoni‐Rossi, Mônica; Scaglia Linhares, Francisco; Costantino, Paolo; Cardarelli, Maura
SUMMARY: Auxin Response Factor 8 plays a key role in late stamen development: its splice variants ARF8.4 and ARF8.2 control stamen elongation and anther dehiscence. Here, we characterized the role of ARF8 isoforms in pollen fertility. By phenotypic and ultrastructural analysis of arf8‐7 mutant stamens, we found defects in pollen germination and viability caused by alterations in exine structure and pollen coat deposition. Furthermore, tapetum degeneration, a prerequisite for proper pollen wall formation, is delayed in arf8‐7 anthers. In agreement, the genes encoding the transcription factors TDF1, AMS, MS188 and MS1, required for exine and pollen coat formation, and tapetum development, are downregulated in arf8‐7 stamens. Consistently, the sporopollenin content is decreased, and the expression of sporopollenin synthesis/transport and pollen coat protein biosynthetic genes, regulated by AMS and MS188, is reduced. Inducible expression of the full‐length isoform ARF8.1 in arf8‐7 inflorescences complements the pollen (and tapetum) phenotype and restores the expression of the above transcription factors. Chromatin immunoprecipitation‐quantitative polymerase chain reaction assay revealed that ARF8.1 directly targets the promoters of TDF1, AMS and MS188 . In conclusion, the ARF8.1 isoform controls pollen and tapetum development acting directly on the expression of TDF1, AMS and MS188, which belong to the pollen/tapetum genetic pathway. Significance Statement: Auxin Response Factor 8 plays a key role in late stamen development and its splice variants, ARF8.2 and ARF8.4, controls stamen elongation and anther dehiscence. Here we demonstrate that the full‐length isoform ARF8.1 has a major role in pollen fertility, and directly regulates the expression of the transcription factors TDF1, AMS and MS188 that belong to the pollen tapetum genetic pathway.